Ḥadīd al-Baṣar in the Thought of Ibn Ḥajar al-Haytamī and Its Implications for Ru’yat al-Hilāl Testimony in Indonesia - Khairul Anaam; M. Basthoni; Maruf Maruf; Ahmad Syifaul Anam; Rupi'i Rupi'i (Fakultas Syari'ah dan Hukum UIN Walisongo, 2026)
The determination of the Islamic lunar month through ru’yat al-hilāl remains contested in Indonesia, particularly when individual testimony conflicts with established visibility criteria (imkān al-ru’yah). This study examines the concept of ḥadīd al-baṣar in the thought of Ibn Ḥajar al-Haytamī and its implications for moon sighting testimony in Indonesia. Using qualitative library research and Fazlur Rahman’s double movement theory, this study reconstructs the historical background of Ibn Ḥajar’s view and contextualizes it within contemporary practice. The findings show that his concept was shaped by Shāfi’ī legal methodology, early astronomical knowledge, and the absence of optical instruments. Testimony based on ḥadīd al-baṣar cannot serve as a general legal basis but may be personally binding. In Indonesia, such testimony is not institutionally accepted when it contradicts official visibility criteria.